ISLAMIC CORPORATE IDENTITY IN THE PRACTICE OF ANNUAL REPORT DISCLOSURE ISLAMIC BANK - Ratih Paramitasari (Assets: Jurnal Akuntansi dan Pendidikan, 2012)
The development of Islamic banking is directed to provide great benefit to society and contribute optimally to the national economy. Islamic banking system and conventional banking system together synergistically supports the mobilization of public funds broadly improve the ability of finance to sectors of national economy. Together with the development of Islamic banking industry in Indonesia, there are many controversies from the community, where most problems highlighted are sticking the label of syariah in Islamic financial institutions are still considered not feasible. Based to these problems, researchers want to conduct this research on the suitability of the annual report disclosure practices of Islamic banks in Indonesia to the reporting standards that reflect the ideal of Islamic Corporate Identity.This study using a checklist for the data analysis consisting of the five themes and the eight dimensions that are should be disclosed in annual reports of Islamic banks. From the results of the assessment aspect of the checklist is then poured in the index EII (ethical identity index). From the calculation of EII, it can be seen that the annual report disclosure practices syariah banks for 2007, 2008, and 2009, has approached the ideal reporting standards that reflect the Islamic Corporate Identity.